2010
DOI: 10.3109/09537104.2010.504869
|View full text |Cite
|
Sign up to set email alerts
|

Newborn platelets: Lower levels of protease-activated receptors cause hypoaggregability to thrombin

Abstract: Newborn platelets show in vitro hypoaggregability to thrombin. Sensitivity of platelets to such a potent agonist is crucial for a functional clot formation. Nevertheless, newborns have an excellent hemostasis. We wanted to investigate the reason for this impairment by comparatively analysing levels of receptors known to be involved in thrombin signaling in newborn and adult platelets. Platelets of adult and cord blood were isolated, washed, and lysed. Resulting protein samples were separated by SDS-PAGE and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…We could show that PAR1 and PAR4 levels are lower in newborn PLTs compared to adult controls and that PAR receptor levels do correlate with PLT aggregation, when initiated with the specific agonist 14 . For the first time we could find a plausible explanation for the hyporeactivity of newborn PLTs to thrombin.…”
mentioning
confidence: 76%
“…We could show that PAR1 and PAR4 levels are lower in newborn PLTs compared to adult controls and that PAR receptor levels do correlate with PLT aggregation, when initiated with the specific agonist 14 . For the first time we could find a plausible explanation for the hyporeactivity of newborn PLTs to thrombin.…”
mentioning
confidence: 76%
“…12 Recently, decreased expression of PAR-1 and PAR-4 receptors was described in neonatal platelets, thus explaining the decreased response to thrombin. 16,17 While this platelet hyporeactivity would have been expected to result in a bleeding tendency, Andrew et al . in 1999 reported that full term neonates had shorter bleeding times (BTs) than healthy adults.…”
Section: Primary Hemostasis In the Neonatementioning
confidence: 99%
“…The reduced response to adrenaline and thrombin has been attributed to decreased receptor expression, and in the case of thromboxane A 2 mimetic U46619, to defective G protein-coupled activity. 10 17 18 …”
Section: Introductionmentioning
confidence: 99%